A sátira na poesia realista portuguesa - Carlos Nogueira (Mélanges de la Casa de Velázquez, 2021)
With the Odes Modernas (1865; 2.nd ed., revised and enlarged, 1875) by Antero de Quental and the Visão dos Tempos (1864) and Tempestades Sonoras (1864) by Teófilo Braga, the so-called Portuguese realist school was inaugurated. This was, in other words, the third period of Romanticism (of the social type, in the style of Hugo and Michelet), whose concept of poetry continued the enterprise of the first generation of Portuguese romantics. This concept involves the attribution to literature of a superior ethical, instructive and progressive function, and of a social, ideological, political and philosophical commitment. In this article I show how satirical poetry, or poetry with satirical tones, from some of the most important Portuguese poets of the mid-nineteenth century, pursues this goal of moralizing customs. I approach authors whose works, although well or reasonably well known, have been little studied in terms of satire, namely Antero de Quental, Guilherme de Azevedo, Bulhão Pato and João de Deus.